2015
DOI: 10.1002/cncr.29805
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in the use of screening magnetic resonance imaging of the breast in community practice by race, ethnicity, and socioeconomic status

Abstract: Background Uptake of breast magnetic resonance imaging (MRI) coupled with breast cancer risk assessment offers the opportunity to tailor the benefits and harms of screening strategies for women with differing cancer risks. Despite the potential benefits, there is also concern for worsening population-based health disparities. Methods Among 316,172 women aged 35-69 years from five Breast Cancer Surveillance Consortium registries (2007-2012), we examined 617,723 negative screening mammograms and 1,047 screenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 31 publications
3
39
0
Order By: Relevance
“…Our study builds on findings by Haas et al, 25 who reported a positive association between advanced education and uptake of supplemental MRI screening services over time. Higher educational attainment may increase personal perception of risk based on family history, which may encourage women in this group to discuss risk reduction with healthcare providers.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Our study builds on findings by Haas et al, 25 who reported a positive association between advanced education and uptake of supplemental MRI screening services over time. Higher educational attainment may increase personal perception of risk based on family history, which may encourage women in this group to discuss risk reduction with healthcare providers.…”
Section: Discussionsupporting
confidence: 75%
“…Higher educational attainment may increase personal perception of risk based on family history, which may encourage women in this group to discuss risk reduction with healthcare providers. 25 Prior studies have also suggested disparities among traditionally underserved groups in gaining access to genetic risk assessment, which may directly impact referral for supplemental breast screening. 26 We found no significant difference in on-site MRI use between women who resided in areas with low household income levels compared to women with higher income levels.…”
Section: Discussionmentioning
confidence: 99%
“…Use of advanced imaging techniques such as breast MR imaging has the potential to exacerbate existing disparities in access to breast cancer screening and diagnostic services. Previous BCSC analyses showed that, among women at high risk, those with lower educational attainment (high school graduate, General Educational Development certificate of high school equivalency, or lower) were 60% less likely to use screening MR imaging compared with women with at least a college degree (25). At the same time, among women at average risk, those with at least a college education were almost 2.5 times more likely to use screening MR imaging.…”
Section: Discussionmentioning
confidence: 97%
“…50 Third, studies have found that risk among black patients receiving delayed and nonstandard treatment is substantially elevated. 51,52 Nevertheless, white women tend to have magnetic resonance imaging targeting breast cancer and genetic testing of high sensitivity. Moreover, they also undergo more aggressive preventive procedures, such bilateral mastectomies, which greatly improve their survival outcomes.…”
Section: Discussionmentioning
confidence: 99%